Blood Synthetic Cannabinoid Concentrations in Cases of Suspected Impaired Driving - Yeakel, J. K.; Logan, B. K. (Journal of analytical toxicology, 2013)
Twelve cases of suspected impaired driving are discussed in which the drivers who subsequently tested positive for synthetic cannabinoid drugs underwent a psychophysical assessment. The attitude of the drivers was described as cooperative and relaxed, speech was slow and slurred and coordination was poor. Pulse and blood pressure were generally elevated. Horizontal gaze nystagmus was assessed in nine of the subjects, but was present in only two. The most consistent indicator was a marked lack of convergence. In all cases where a Drug Recognition Expert (DRE) officer evaluated and documented impairment (10 cases), it was attributed to the DRE cannabis category. Performance in field sobriety tests was variable, ranging from poor to minimal observable effect. Synthetic cannabinoid testing was performed by LC-MS-MS. Positive results included: JWH-018 (n = 4), 0.1-1.1 ng/mL; JWH-081 (n = 2) qualitative only; JWH-122 (n = 3), 2.5 ng/mL; JWH-210 (n = 4), 0.1 ng/mL; JWH-250 (n = 1), 0.38 ng/mL and AM-2201 (n = 6), 0.43-4.0 ng/mL. While there is good evidence of psychophysical impairment in these subjects, further structured data collection is needed to fully assess the relationship between synthetic cannabinoid use and psychomotor and cognitive impairment.